Stories of being a new nurse academic at a nursing education institution - Linda Mutenga; Charlené Downing; Irene J. Kearns (Wiley, 2023)
Abstract Objectives The objectives of this study were to explore and discover the best moments of being a new nurse academic at nursing education institutions. Aim The purpose of this study was to define, discover and learn about the experiences of being a new nurse academic. Design A qualitative design with inspiration from Appreciative Inquiry (AI) was used. Method Purposive and snowball sampling was used. Data collection was done using semi‐structured individual interviews. Data were analysed using Giorgi's method. The COREQ guidance was used for reporting of this study. Results Four themes were identified. (1) The emphasis was their transition from clinical setting into the world of academics, which was challenging, overwhelming and exciting all at the same time. (2) Participants were fulfilled and influenced to achieve more. (3) Participants expressed what they wished for. (4) Participants shared recommendations for job security, employment and retainment of new nurse academics.